Foundations of Molecular Modeling and Simulation Select Papers from FOMMS 2015 - Snurr, Randall Q.; Adjiman, Claire S.; Kofke, David A. (Molecular Modeling and Simulation, Applications and Perspectives, 2016)
This book is a collection of select proceedings of the FOMMS 2015 conference. FOMMS 2015 is the sixth triennial FOMMS conference showcasing applications of theory of computational quantum chemistry, molecular science, and engineering simulation. The theme of the 2015 meeting focuses on Molecular Modeling and the Materials Genome.